2005
DOI: 10.1162/15353500200505118
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism of Human Prostate Cancer Mouse Xenografts

Abstract: We hypothesized that the glucose metabolism of prostate cancer is modulated by androgen. We performed in vivo biodistribution and imaging studies of [F-18] 49.418 Â day À 753.33, R 2 = .96, n = 3). The FDG accumulation in the CWR-22 tumor implanted in the castrated mice was significantly lower, by an average of 55%, in comparison to that implanted in the noncastrated host (1.27 vs. 2.83, respectively, p < .05). The 3-week maximal standardized uptake value (SUV max ) was 0.99 ± 0.43 (mean ± SD) for CWR-22 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 40 publications
1
41
1
Order By: Relevance
“…Comparable results in CWR22 mice were found for 18 F-FLT before and after castration by Oyama et al (14). In CWR22 and PC-3 tumors, we found a 18 F-FDG T/M that was approximately a factor of 2 higher than the one reported by Jadvar et al (32). Krause et al showed in a PC-3 tumor model a T/M of 1.8 6 0.4 before treatment and was able to monitor with 11 C-choline a therapy response when using docetaxel (33).…”
Section: Discussioncontrasting
confidence: 48%
“…Comparable results in CWR22 mice were found for 18 F-FLT before and after castration by Oyama et al (14). In CWR22 and PC-3 tumors, we found a 18 F-FDG T/M that was approximately a factor of 2 higher than the one reported by Jadvar et al (32). Krause et al showed in a PC-3 tumor model a T/M of 1.8 6 0.4 before treatment and was able to monitor with 11 C-choline a therapy response when using docetaxel (33).…”
Section: Discussioncontrasting
confidence: 48%
“…Early changes in 18 F-FDG accumulation compared with volume changes were also seen by Leyton et al, who studied the efficacy of the cytotoxic agent cisplatin in an 18 F-FDG microPET study (13). Their study showed a difference in 18 F-FDG accumulation between the drugtreated and control groups at 24 h, whereas a difference in tumor volume was seen later at 48 h. Several other groups (8,(10)(11)(12) have tracked changes in tumor volume and 18 F-FDG accumulation; however, unlike the current study, no direct statistical comparisons were made in any of these prior studies to assess which changes occurred earlier.…”
Section: Ce-355621 Inhibits 18 F-fdg Accumulation In U87 Mg Xenograftsmentioning
confidence: 55%
“…With the development of microPET scanners for small animals (5), assessment of tumor xenograft mouse models with 18 F-FDG became possible for preclinical oncology research. Several authors have used 18 F-FDG microPET to assess various therapies in mouse tumor xenograft models (6)(7)(8)(9). In addition, several studies have compared 18 F-FDG microPET with an alternative proliferation tracer, 39-deoxy-39- 18 F-fluorothymidine ( 18 F-FLT), to assess tumor xenograft response to a variety of therapies (10)(11)(12)(13).…”
Section: Ce-355621 Is a Novel Monoclonal Antibody That Bindsmentioning
confidence: 99%
“…This further underlines the importance of considering the microenvironment, which potentially modulates intracellular metabolism [152]. Additionally, high grade (Gleason > 7) and castration-resistant tumors seem to reactivate glycolysis, since FDG-PET and FDG-PET/CT studies indicate an increased glucose uptake compared to benign and low stage prostate cancers [153][154][155][156][157]. Accordingly, prostate cancer is affected by 2-deoxyglucose [158][159][160].…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 98%